Pengaruh Kualitas Laba dan Tingkat Efisiensi Operasional Terhadap Kinerja Keuangan Perusahaan Perbankan - Difqi, Difqi; Kartini, Tina; Nurmilah, Risma (PT Alahyan Publisher Sukabumi, 2025)
This study aims to analyze the effect of earnings quality and operational efficiency on the financial performance of conventional banking companies listed on the Indonesia Stock Exchange (IDX) during the 2022-2024 period. The research population consists of 58 conventional banks, with a sample of 15 banks selected using purposive sampling based on the availability of complete financial reports and consistent listing on the IDX. The observation period covers three years, resulting in 45 observations. Earnings quality is measured by earnings persistence, earnings predictability, and the ratio of operating cash flow to net income. Operational efficiency is measured using the BOPO ratio, while financial performance is proxied by Return on Assets (ROA). Data analysis was conducted using a quantitative approach indicate that earnings quality has a significant positive effect on financial performance, operational efficiency has a significant negative effect on financial performance, and simultaneously both variables significantly influence the financial performance of conventional performance of conventional banks. These findings highlight the importance of improving earnings quality and operational efficiency as strategies to maintain profitability and competitiveness in Indonesia’s conventional banking sector.